Determinants of innovation: A multivariate analysis in Colombian micro, small and medium-sized enterprises (2018)
Purpose – This paper aims to study the influence of innovation on micro, small and medium-sized enterprises (MSME) performance in Colombia through the 403 MSMES survey analysis. In particular, this paper measures the effect of participation in R&D alliances, product innovation and process innovation on it. Design/methodology/approach – MSME performance is measured through a composite index, estimated through principal components analysis using polychoric correlations, which is based on eight selfreported assessments of MSME performance. Then, this measure of performance is related to MSME participation in R&D alliances and the product and process development stance of the MSME based on an adaptation of the Miles and Snow business classification scheme, by means of an ANOVA and a linear regression. Findings – Colombian SMEs are not significantly benefitted from participation on R&D alliances. Instead, their performance appears to be dependent upon their internal innovation efforts directed to product development. Moreover, the results suggest that imitators get a performance almost as high as innovators. Originality/value – Innovation activities in Colombian SMEs are carried out informally, as they are mostly uninterested to engage in R&D activities and to develop new products by own initiative. Moreover, few of them have an R&D department. In regard to technology, results suggest that almost half of SMEs are classified as followers, namely, they use the same technology as competitors. Keywords Innovation, MSME performance, Product and process innovation, Alliances, ANOVA